1998
DOI: 10.1161/01.hyp.32.6.1016
|View full text |Cite
|
Sign up to set email alerts
|

Basal and Stimulated Sympathetic Responses After Epinephrine

Abstract: Abstract-Delayed facilitation of norepinephrine release through the action of epinephrine (NE) at presynaptic ␤-adrenoceptors has been postulated to account for the delayed hemodynamic effects of epinephrine and to be a mechanism causally related to the development of hypertension. To determine whether a short-term increase in epinephrine concentrations resulted in subsequent facilitation of sympathetic responses, 9 healthy subjects (age, 21Ϯ0.9 years) were studied at rest and during physiological stress on 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Although the injection of saline and epinephrine is frequently used in liposuction, few experimental studies were found in the literature. 15,16 The late deaths (after 48 hours) were not expected because we believed that epinephrine had a short-lasting action. 14 Our study conducted in rabbits demonstrates that a dose of 1.21mg/kg of body weight was safe when injected subcutaneously in the abdominal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the injection of saline and epinephrine is frequently used in liposuction, few experimental studies were found in the literature. 15,16 The late deaths (after 48 hours) were not expected because we believed that epinephrine had a short-lasting action. 14 Our study conducted in rabbits demonstrates that a dose of 1.21mg/kg of body weight was safe when injected subcutaneously in the abdominal region.…”
Section: Discussionmentioning
confidence: 99%
“…3,12,13 All aspects of the changes caused by epinephrine in the human body have been widely published in the literature. 1,[14][15][16] Countless studies on the dose of epinephrine have considered only the intravenous administration. Because of its frequent use in surgery, particularly in plastic surgery, after the introduction of liposuction by Illouz in 1977 for the treatment of lipodystrophy and body contouring and because of the increase in the number of this type of surgery, there has been also a need to increase the dose of epinephrine in combination with the anesthetic substance for subcutaneous administration.…”
Section: Issn: 2770-7636mentioning
confidence: 99%